Achieving Super Broadband Electromagnetic Absorption by Optimizing Impedance Match of rGO Sponge Metamaterials. (22nd October 2021) - Sun, Xianxian; Li, Yibin; Huang, Yixing; Cheng, Yuanjing; Wang, Shasha; Yin, Weilong
Abstract: The reduced graphene oxide (rGO) sponges exhibit exciting electromagnetic absorption (MA) performance in high‐frequency range. However, it is still a great challenge to realize desirable MA property at low frequency (2–4 GHz) due to the great difficulty in balancing the good interfacial impedance matching and strong dielectric loss. Herein, the MA metamaterials based on rGO sponge with different unit shapes are reported. The relationship between the unit shape and MA performance is explored by experiment and simulation. The results show that frustum pyramid metamaterial exhibits ultrabroad band MA; the qualified absorption (the reflection loss lower than −10 dB) of electromagnetic wave can be achieved at 2.4–40 GHz. The average absorption intensity is −22.9 dB in the band of 2–40 GHz. Moreover, the bandwidth for strong absorption with an absorption rate of 99% (−20 dB) is up to 32 GHz. It is significant that the reflection loss has ignorant change even though the incident angle is increased from 5° to 40°. These are contributed to the excellent impedance matching and strong dielectric loss. These lightweight frustum pyramid metamaterials are very promising in the application for broadband electromagnetic protection. Abstract : The electromagnetic absorption metamaterials based on reduced graphene oxide (rGO) sponge with different unit shapes (sphere, cubic, hexagonal prism, and frustum pyramid) are prepared. The relationship between the unit shape and electromagnetic absorption performance is explored by experiments and simulation. The frustum pyramid metamaterial exhibits ultrabroad band electromagnetic absorption, which is contributed to the excellent impedance matching.